2020
DOI: 10.4103/ijciis.ijciis_64_19
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic injuries associated with suicide attempts: A retrospective study from single national level 1 trauma center

Abstract: Background: Suicide is a complex phenomenon involving several risk factors. We aimed to describe the frequency, pattern, and outcomes of patients with traumatic injuries following suicide attempts admitted to a level 1 trauma center. Methods: We conducted a retrospective analysis of data obtained from Qatar National Trauma Registry and mortuary database. The study included all patients with traumatic injuries following suicide attempts, admitted to the Hamad Trauma Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Akin to previous studies, 7,10,29,30 the study found teenagers who attempted suicide were 1.5 times more likely to be seriously injured than peers who did not attempt suicide. Some studies also established the predictive effect of suicidal ideation on the occurrence of injuries, 6,10,12,13 which was not found in the current study even after adjusting for other variables.…”
Section: Discussionmentioning
confidence: 63%
“…Akin to previous studies, 7,10,29,30 the study found teenagers who attempted suicide were 1.5 times more likely to be seriously injured than peers who did not attempt suicide. Some studies also established the predictive effect of suicidal ideation on the occurrence of injuries, 6,10,12,13 which was not found in the current study even after adjusting for other variables.…”
Section: Discussionmentioning
confidence: 63%
“…However, they do state a concern about underestimating self-inflicted injuries due to nontrauma activated penetrating injuries (Bukur et al, 2011). Al-Thani et al (2020) used the Qatar National Trauma Registry, excluding nonsuicidal self-injury but making no distinction between intentional and unintentional injuries. In another characterization of suicide attempts at a trauma center, Hadjizacharia et al (2010) recognized the limitations of the ICD-9 as possibly missing “a number of patients who presented with injuries that were not classified as self-inflicted” (p. 417).…”
Section: Discussionmentioning
confidence: 99%